Post war city (2009)
The following article analyzes the post war city from different aspects by which the city is affected -economy, population, culture and identity. To develop such analysis, the author concentrates on the city of Warsaw under the context of Second World War, where a group of individuals, risking their lives, reconstruct the identity and the memory of a city. In addition, it is outlined the intervention of different disciplines in the development of the city as a project.